A load cell for grain-propelled ballistic rocket thrust measurement - De Lucena, Samuel E. [UNESP]; De Aquino, Marcelo G. S.; Caporalli-Filho, Angelo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
A 1000-kgf resistive strain-gauge load cell has been developed for quality testing of rocket propellant grain. A 7075-T6 aluminum alloy has been used for the elastic column, in which 8 uniaxial, 120-Ω strain gauges have been bonded and connected to form a full Wheatstone bridge to detect the strain. The chosen geometry makes the transducer insensitive to moments and, also, to the temperature. Experimental tests using a universal testing machine to imposed compression force to the load cell have demonstrated that its behavior is linear, with sensitivity of 2.90 μV/kgf ± 0.34%, and negligible hysteresis. The designed force transducer response to a dynamic test has been comparable to that of a commercial load cell. © 2005 IEEE.
Keywords: Force measurement; Force transducer; Load cells; Load measurement; Rockets; Strain gauge; Thrust measurement; Force transducers; Universal testing machine; Aluminum alloys; Hysteresis; Military rockets; Propellants; Strain gages; Structural loads